Development of Learning Media for Ethnomathematics and Culture of Lampung with the Powtoon Application - Choirudin Choirudin; Eka Fitria Ningsih; Hanif Amrulloh; Muhammad Saidun Anwar; Isnaini Nur Azizah; Mega Suaedah Prastika (Institut Agama Islam Negeri (IAIN) Tulungagung, 2020)
This study aims to develop Mathematics learning media using ethnomathematics based Powtoon applications. This study is using the Borg and Gall development model. Media development is carried out on the material of a flat triangle and quadrilateral of Class VII Junior High School. Data collection instruments used were media expert questionnaires, material experts used to test the quality of mathematics-based Powtoon learning media, and student response questionnaires to test interest in the developed media. Data collection methods used the form of interviews, documentation and questionnaires. This research resulted in ethnomathematics based Powtoon learning media. The results of the assessment by media experts scored 88% in the very feasible category, the assessment of the material experts obtained a score of 87% in the very feasible category, while based on trials in class VII students of Ma'arif 1 Metro SMP which amounted to 22 students obtained a score of 80% with the eligible category. The development of ethnomathematics based Powtoon learning media is feasible and can be used by teachers and students as learning media.